Why Are the Poor More Vulnerable to Bribery in Africa? The Institutional Effects of Services. Issue 1 (2nd January 2018) - Peiffer, Caryn; Rose, Richard
Abstract: Whereas most studies find the poor in Africa to be more vulnerable to bribery because of their lower socio-economic status, this paper proposes institutional differences as an alternative explanation. Because poor people are unable to afford privately provided services, they must use public services. In relying on the state more often, the poor become more vulnerable to bribery. Analyses of Afrobarometer data show that the poor are not more likely to pay bribes for state monopolised services. The poor's disproportionate vulnerability to bribery for choice services is a function of their greater likelihood to have contact with the state.